ANALISIS FINANCIAL DISTRESS BAGI PERUSAHAAN MANUFAKTUR YANG LISTED DI BURSA EFEK INDONESIA SEBAGAI DAMPAK KRISIS EKONOMI ASIA - Hidayat, Widi (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
The impact of economic crisis in Asia is financial distress for manufacturing companies listed in Bursa Efek Indonesia. The indicator of external factors is inflation rate, interest rate and exchange rate rises and causation the investment, financial and dividend decision be careful.          The indicator of Internal Financial Decision is Profitability, fixed asset utilization, capital intensiveness, inventory intensiveness and receivable intensiveness declined and leverage still high. Deficit free cash flow and shareholder wealth is dividend yield and capital gain yield declined.          Manufacturing companies must be reinventing the strategy of financial decision because investment risk is higher. Government especially Bank Indonesia and BAPEPAM to make regulation macro economic variable, because the effect of higher inflation rate, interest rate, and exchange rate could be declined purchasing power of society and rises the cost of good manufacturing and added unemployment. Keywords :   inflation rate, interest rate, exchange rate, internal financial decision, financial distress.